Impact of postoperative radiation therapy for deeply invasive oral cavity cancer upstaged to stage III. Issue 5 (18th February 2019) - Cramer, John D.; Samant, Sandeep; Heron, Dwight E.; Ferris, Robert L.; Kim, Seugwon
Abstract: Background: This article is about the eighth edition staging guidelines for upstaged patients with oral cavity squamous cell carcinoma (OCSCC) with >10 mm depth to pT3. This upstages some patients from stage I‐II to stage III, a point at which patients are traditionally considered for postoperative radiation therapy (PORT). The role of PORT in patients upstaged for >10 mm depth is unknown. Methods: We identified patients with surgically resected stage I‐II OCSCC with >10 mm depth who were upstaged to stage III. We used Cox proportional hazard modeling to compare patients who received PORT to those who did not (median follow‐up 38.6 months). Results: We observed that 3.6% of patients with OCSCC were upstaged to stage III for depth >10 mm including 823 eligible patients. On adjusted analyses, PORT was associated with improved overall survival in patients upstaged to stage III (adjusted hazard ratio [aHR] 0.47, 95% confidence interval [CI] 0.30‐0.73). Conclusion: PORT is associated with improved survival for patients with OCSCC upstaged to stage III for >10 mm depth.